Virtual wall–based haptic-guided teleoperated surgical robotic system for single-port brain tumor removal surgery. (January 2017) - Seung, Sungmin; Choi, Hongseok; Jang, Jongseong; Kim, Young Soo; Park, Jong-Oh; Park, Sukho; Ko, Seong Young
This article presents a haptic-guided teleoperation for a tumor removal surgical robotic system, so-called a SIROMAN system. The system was developed in our previous work to make it possible to access tumor tissue, even those that seat deeply inside the brain, and to remove the tissue with full maneuverability. For a safe and accurate operation to remove only tumor tissue completely while minimizing damage to the normal tissue, a virtual wall–based haptic guidance together with a medical image–guided control is proposed and developed. The virtual wall is extracted from preoperative medical images, and the robot is controlled to restrict its motion within the virtual wall using haptic feedback. Coordinate transformation between sub-systems, a collision detection algorithm, and a haptic-guided teleoperation using a virtual wall are described in the context of using SIROMAN. A series of experiments using a simplified virtual wall are performed to evaluate the performance of virtual wall–based haptic-guided teleoperation. With haptic guidance, the accuracy of the robotic manipulator's trajectory is improved by 57% compared to one without. The tissue removal performance is also improved by 21% ( p < 0.05). The experiments show that virtual wall–based haptic guidance provides safer and more accurate tissue removal for single-port brain surgery.